Association between distal radius fracture malunion and patient-reported disability : a systematic review and meta-analysis - Ali, Muhanned ; 0000-0002-1023-712X; Rosales, Roberto S.; Brogren, Elisabeth; Waldén, Markus; Nordenskjöld, Jesper; Atroshi, Isam (EFORT Open Reviews, 2024)
• Purpose: To assess whether distal radius fracture (DRF) malunion is associated with greater patient-reported disability. • Methods: We searched PubMed, EMBASE, and Cochrane databases up to 21 May 2023. Two reviewers independently screened retrieved titles/abstracts and assessed the full text of potentially eligible articles to identify cohort studies and randomized controlled trials reporting outcomes of DRF in adults at least 12 months after fracture, confirmed radiologically 3 months or longer after fracture. We excluded studies not reporting patient-reported outcomes according to malunion and studies judged to have a high risk of bias, as assessed independently by two reviewers using the Quality In Prognosis Studies tool. To express the overall effect of malunion on patient-reported disability, we calculated the standardized mean difference (SMD) with a 95% CI. • Results: Six studies with 898 patients (77% women) were included; five involved adults of all ages, and one restricted to patients aged 65 years and older. In the meta-analysis including the five studies with adults of all ages (1047 observations), the SMD was 0.58 (95% CI: 0.42–0.74; P < 0.001), favoring no malunion, with no statistically significant heterogeneity or publication bias. In the meta-analysis including all six studies (1193 observations), the SMD was 0.51 (95% CI: 0.35–0.67; P < 0.001), favoring no malunion, with moderate but significant heterogeneity. • Conclusion: Malunion of distal radius fracture is associated with significantly greater patient-reported disability with a moderate magnitude in terms of clinical importance. The study does not address the possible influence of age or treatment methods.
Keywords: distal radius fracture; malunion; patient-reported outcomes; systematic review